The Peru's participation in the security council during the twentieth century - Morote Canales, Ricardo (2021)
This work shows the three occasions in which Peru, as a founding member of the United Nations, has constructively participated in the Security Council (1955 - 1956), (1973 - 1974) and (1984 - 1985) and always guided by the principles and purposes of the United Nations Charter to achieve international peace and security. The most relevant thematic axes in this period are those referred to human rights, civil and political rights, international security, decolonization, and people´s self[1]determination. Among the main issues developed herein are the Palestinian question and the Middle East, the Suez Canal crisis, Apartheid and decolonization in Southern Africa, the question of Cyprus, and the Nicaragua matter. These issues took decades to resolve, and some persist until today. Likewise, it can be seen that the interaction between the States and the United Nations, through the resolutions and decisions of the General Assembly and the Security Council, as well as the advisory opinions and jurisprudence of the International Court of Justice, are laying the foundations of modern treaty law, jurisprudence and doctrine, generating the evolution and further development of International Law characterized by the establishment of substantive complementary instruments to the United Nations Charter.